APPLICATION OF MODERN ICT TO SHAPE INDIVIDUAL EDUCATIONAL REFLECTIVE AND HUMANISTIC TRAJECTORY OF DEVELOPMENT OF THE PUPIL OF SECONDARY SCHOOL - Mukiy, Т.В. (Journal of Information Technologies in Education (ITE), 2015)
The widespread use of ICT in everyday life gives opportunities for acquiring of quality integrated knowledge in different fields, remote data management, self-education that improves and simplifies the life of modern man on the one hand. And on the other it’s caused the appearance of new psychological problems of value-motivational, cognitive, psycho-physical areas of the child’s personality due to the lack of skills of large information flow filtering. The uncontrolled behavior and mind manipulation through reflexive inability to comprehend the meaning of information resources of inhumane nature exposes a child to danger. In some way it leads to a child’s dependence on the computer and the Internet. In solving of above mentioned problems crucial importance is gained by qualities of intellectual, reflective, spiritual and humanistic potential of pupil’s personality in particular – forming of reflexive-humanistic educational development trajectory of the child’s development. Urgent problem that becomes for teacher of Informatics is the humanization of the educational process through the implementation of educational, computerbased learning tools that will develop reflexivity and humanistic pupil’s potential. The article deals with the special aspects of formation of humanistic reflexive-educational trajectory of the pupil’s development during studying Informatics at secondary school, it presents the systematization of specified definitions’ components. Ways of using the modern information and communication technologies for comprehensive harmonious development of a child’s personality in the global informatization are substantiated and generalized.